2017
DOI: 10.1016/j.marpol.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Safety and CO2 emissions: Implications of using organic fluids in a ship’s waste heat recovery system

Abstract: Current Marine Policies and regulations greatly favour the use of efficiency enhancing technologies such as the Organic Rankine Cycle (ORC) waste heat recovery systems (WHRS), through the entry into force of International Maritime Organisation (IMO) Energy Efficiency Design Index (EEDI). However, safety regulations such as IMO Safety Of Life At Sea (SOLAS), International Gas Code and Classification Societies still consider the use of highly flammable organic fluids on board ships as hazardous and undesirable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…However, it is also useful to consider and anticipate some of the barriers that may be preventing greater levels of uptake of emission reducing technologies now, and that may further hinder, or increase the cost of, deep decarbonisation in the future. Suárez de la Fuente et al [14] describe how waste heat recovery systems can reduce energy demand, but also potentially conflict with existing safety regulations. These regulations are a product of the historic design and operation of ships, yet both have been superseded by the now commonplace use of unmanned machinery spaces, rendering the regulations less justified.…”
Section: Deep Decarbonisation Of Shipping: Barriers and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also useful to consider and anticipate some of the barriers that may be preventing greater levels of uptake of emission reducing technologies now, and that may further hinder, or increase the cost of, deep decarbonisation in the future. Suárez de la Fuente et al [14] describe how waste heat recovery systems can reduce energy demand, but also potentially conflict with existing safety regulations. These regulations are a product of the historic design and operation of ships, yet both have been superseded by the now commonplace use of unmanned machinery spaces, rendering the regulations less justified.…”
Section: Deep Decarbonisation Of Shipping: Barriers and Opportunitiesmentioning
confidence: 99%
“…Whilst this special issue is not focused on the identification and analysis of decarbonisation pathways themselves, a number of papers suggest promising technology and operational options. These include a concerted effort for slow (or even ultraslow) steaming [10], the use of waste heat recovery as mentioned previously [14], and the use of wind-assistance technology [10,12]. In some instances there are synergies that can occur (e.g.…”
Section: Deep Decarbonisation Of Shipping: Barriers and Opportunitiesmentioning
confidence: 99%
“…The IGF recommends the use of double-walled piping, ventilation for the enclosed space to the atmosphere, gas detection and firefighting systems according to the fluid used. Equally important are personnel training, risk management (e.g., enclosed space management system, see Allan 2015) and assessments and safety procedures in case of fire or leakages (Suárez de la Fuente et al 2015). The safety requirements for the marine ORC WHRS selected will increase the initial cost and maintenance costs, but performance may also be affected.…”
Section: Safety On Boardmentioning
confidence: 99%
“…Quoilin et al (2013) show that the cost of an ORC WHRS module of the size proposed in this paper should be less than £1,640 per kW e 3 , while for an RC WHRS the cost can range between £688 and £862 per kW e (BCS Incorporated 2008). However, the WHRS payback period can be less than three years for any of the cycles tested (Suárez de la Fuente et al 2015). Thus, the installation of a WHRS is an economically-viable green technology.…”
Section: Short-and Long-term Marine Whrs Benefitsmentioning
confidence: 99%
“…In terms of power production, the ORC unit outperformed the other two, while the SRC unit ranked high in qualitative assessments concerning working fluid safety, environmental properties and familiarity of the technology. Other authors [21][22][23][24] compared the off-design performance of single pressure SRC and ORC systems, for recovery of exhaust gas heat only [21,22], for recovery of exhaust gas and scavenge air heat [23] and for recovery of exhaust gas, scavenge air and jacket water heat [24]. These studies all found that the ORC systems achieved higher performance than the single pressure SRC systems.…”
Section: Introductionmentioning
confidence: 99%